Percepção além da cognição: experiências por detrás das telas de uma sala de controle - Michelle Karine Figueiredo (2015)
The last decades have been marked by a significant increase in activities through computerized systems and, consequently, changes occurred in the embodiment of labor, therefore, the worker before immersed in the "floor manufacture" and in actual contact with the field, it is taken to control rooms, where it operates and monitors machinery, equipment and processes that are miles away. This new configuration of the work attracted the interest of researchers from different areas who were interested in investigating and understanding the actions and perceptions of workers within that "virtual" framework. According to many of these studies, the computerization of work has profoundly changed the way employees relate to the object of their activity, favoring thus the development of intellective skills in place of body, extending the calculation capacity and memory of workers and generating new questions about the need to regulate the cognitive workload to avoid accidents and improve productivity. Thus, these studies include the computerized job as a predominantly cognitive activity, where problems are solved through analytical thinking in a similar way to a computer program, and where you can optimize the creation of graphical interfaces to match the tasks and the inherent capabilities of the worker's mind. The present study questions this predominantly cognitive vision through ethnographic-inspired research into the working practices in a control room of a power company in the State of Minas Gerais, where are remotely controlled power plants and substations. To analyze this empirical case, this study was based on the phenomenology of Merleau-Ponty perception and the concept of intuitive expertise proposed by Hubert and Stuart Dreyfus. From this analysis, this study argues that even in a fully computerized activity, actions and perceptions of experienced workers are not things that happen in a logical and analytical way by cognitive assumption. Moreover, it was observed that due to practical experiences, skills become incorporated and the worker is able to realize meaningfully and act in a natural way through the body. With this proposal, this study shows that, the control room operators, by incorporating the computerized interfaces in their phenomenological field (i.e. sink in that experience through their bodies) they are able to see "beyond" the computer screen. Understand that workers develop expertise through practical experiences can contribute positively to improve the way organizations see human-machine interface and thereby upgrade the way the trainings are proposed, and rules and graphical interfaces are formulated which go beyond universal prescriptions on the cognitive ability of workers.